Peningkatan Hasil Belajar IPS melalui Model Pembelajaran Bamboo Dancing Murid Kelas VI A UPT SPF SD Inpres Bangkala II Kota Makassar - Rahmi Eka Saputri; Nursalam; Hidayah Quraisy (PT PUSTAKA CENDEKIA GROUP, 2024)
Classroom Action Research aims to find out whether the application of the bamboo dancing learning model can improve the learning outcomes of VI A UPT SPF SD Inpres Bangkala II students, Makassar City. The research subjects were 23 students. The research procedure consists of 4 stages each cycle, namely planning, implementing actions, observing and reflecting. The indicator of learning outcomes in this research is the achievement of classical learning completeness. The data collection was carried out using techniques: documentation, observation and tests. The data analysis technique in this research uses qualitative data analysis. The results of the research showed that there was an increase in student activity, namely in cycle I student learning activity was in the good category and in cycle II it increased to the very good category. In cycle I, an average score of 73.48 was obtained with learning completeness of 57%. In cycle II the average score increased to 84.57 with 86% completeness. Based on the results of the research that has been carried out, the conclusion in this research is that the application of the bamboo dancing model can improve the social studies learning outcomes of class VI A students at UPT SPF SD Inpres Bangkala II Makassar City.